OIL PRICES, EXCHANGE RATE VOLATILITY AND FDI INFLOWS ON THE ECONOMIC GROWTH OF GHANA: WAVELET TECHNIQUE AND ARDL APPROACH - Atsi, Eugene Ray (PEOPLE: International Journal of Social Sciences, 2025)
Ghana, like many other developing economies, is intricately connected to global economic trends and fluctuations. This paper investigates the influence of oil prices, exchange rate volatility and FDI inflows on Ghana’s economic growth. Moreover, it determines the level of interdependencies and the lead/lag connectedness among the variables. The study utilizes time series data from 1995 to 2022 and applies the Autoregressive Distributed Lag (ARDL) model as well as Wavelet Multiple techniques (Wavelet Multiple Correlation (WMC) and Wavelet Multiple Cross-Correlation (WMCC)). Based on the ARDL model, oil prices and exchange rate volatility adversely impact Ghana’s GDP. However, FDI inflows reveal a positive and significant relationship to GDP. Using the Wavelet model, the WMC result demonstrates stronger interdependence among the variables. Finally, the outcome from WMCC indicates that the exchange rate is the dominant variable without any lag that plays a pivotal role in determining the coherence among the economic indicators. Therefore, the study suggests that investment in renewable energy, diversification of export products and markets, enhancement of exchange rate framework, promotion of local content and linkages, and monitoring and evaluation of anti-corruption measures should be encouraged to boost the economy of Ghana.